Varian Kualitatif Kacang Tanah Hasil Kultur in Vitro dan Hasil Seleksi in Vitro (Qualitative Variants of Peanut Plants Obtained from in-Vitro Culture and in-Vitro Selection) - Enni Suwarsi Rahayu; Sudarso - (Biosaintifika: Journal of Biology & Biology Education, 2009)
issue cultures that have passed callus phase can induce somaclonal variation, of which the intensity was influenced by the addition of selective agents to culture media. Somaclonal variations of peanut plant obtained from in-vitro cultured and in-vitro selected somatic embryos using PEG was not yet understood. The objectives of this research were 1) to identify the qualitative variants of peanut plant var. Kelinci obtained from in-vitro cultured and in-vitro selected somatic embryos using PEG, 2) to estimate the factors that control the qualitative variants. The non-selected and the selected variant somatic embryos of peanut were germinated and cultured. From fertile R0 lines, sufficient number of R1 and R2 progenies were grown for evaluation. The results showed that phenotypic variations of qualitative characters can be observed among R0, R1 and R2 generations of somaclonal lines. Variant phenotypes of qualitative characters can be observed, these include wide branching, excessive branching, leaf variegation, leaflet number abnormality, leaf pointed tip, ‘rosette’ leaf, complete sterility and partial sterility. The data indicated that wide branching, excessive branching, leaflet number abnormality, partial sterility and complete sterility were genetically controlled, while variant phenotypes of ‘rosette‘ leaf, leaf variegation, and leaf pointed tip were epigenetically controlled. Key words: somaclonal variant, qualitative characters, in vitro selection, in vitro culture